Effects of Leucosporidium‐derived ice‐binding protein (LeIBP) on bull semen cryopreservation - Hoon Jang; Hyo J. Kwon; Wu S. Sun; Seongsoo Hwang; In S. Hwang; Sungwoo Kim; Jun H. Lee; Sung G. Lee; Jeong W. Lee (Veterinary Medicine and Science, 2020)
Abstract We examined the effect of ice‐binding protein derived from Leucosporidium (LeIBP) on the cryopreservation of bull semen and compared it with that derived from previously reported Antifreeze Protein III (AFPIII). Six concentrations of LeIBP (10–1 ~ 104 μg/ml) and AFPIII (10–1 ~ 104 μg/ml) were added to the bull semen extender, respectively. Sperm kinematic parameters were measured to examine sperm toxicity and cryopreserved sperm quality. Measures of antioxidant activity such as superoxide dismutase (SOD), reduced glutathione/oxidative glutathione (GSH/GSSG), and total antioxidant capacity (TAC) were analysed to identify the effect of LeIBP on sperm quality. In addition, sperm viability was analysed using a flow cytometer and fluorescence microscope by SYBR14/PI staining. The results showed that the LeIBP groups (0.1, 1 and 10 μg/ml) were less toxic, and the quality of the sperm were dramatically improved in the extenders containing 0.1 μg/ml LeIBP among concentrations of LeIBP and AFPIII. The SOD activity of LeIBP was greater than that of AFPIII and control. In addition, sperm viability was enhanced in the LeIBP‐treated group. In summary, LeIBP is a useful cryoprotective adjuvant for bull sperm cryopreservation, and the most efficient concentration of LeIBP is 0.1 μg/ml.